Physics book: CRYRING@ESR - Lestinsky, M.; Andrianov, V.; Aurand, B.; Bagnoud, V.; Bernhardt, D.; Beyer, H.; Bishop, S.; Blaum, K.; Bleile, A.; Borovik, A.; Bosch, F.; Bostock, C.; et al. (Springer, 2016)
The exploration of the unique properties of stored and cooled beams of highly-charged ions as provided by heavy-ion storage rings has opened novel and fascinating research opportunities in the realm of atomic and nuclear physics research. Since the late 1980s, pioneering work has been performed at the CRYRING at Stockholm (Abrahamsson et al. 1993) and at the Test Storage Ring (TSR) at Heidelberg (Baumann et al. 1988). For the heaviest ions in the highest charge-states, a real quantum jump was achieved in the early 1990s by the commissioning of the Experimental Storage Ring (ESR) at GSI Helmholtzzentrum für Schwerionenforschung (GSI) in Darmstadt (Franzke 1987) where challenging experiments on the electron dynamics in the strong field regime as well as nuclear physics studies on exotic nuclei and at the borderline to atomic physics were performed. Meanwhile also at Lanzhou a heavy-ion storage ring has been taken in operation, exploiting the unique research opportunities in particular for medium-heavy ions and exotic nuclei (Xia et al. 2002).